p53 isoform Δ113p53 promotes zebrafish heart regeneration by maintaining redox homeostasis - Ye, Shengfan; Zhao, Ting; Zhang, Wei; Tang, Zimu; Gao, Ce; Ma, Zhipeng; Xiong, Jing-Wei; Peng, Jinrong; Tan, Wei-Qiang; Chen, Jun (Cell death & disease, 2020)
Neonatal mice and adult zebrafish can fully regenerate their hearts through proliferation of pre-existing cardiomyocytes. Previous studies have revealed that p53 signalling is activated during cardiac regeneration in neonatal mice and that hydrogen peroxide (H 2 O 2 ) generated near the wound site acts as a novel signal to promote zebrafish heart regeneration. We recently demonstrated that the expression of the p53 isoform Δ133p53 is highly induced upon stimulation by low-level reactive oxygen species (ROS) and that Δ133p53 coordinates with full-length p53 to promote cell survival by enhancing the expression of antioxidant genes. However, the function of p53 signalling in heart regeneration remains uncharacterised. Here, we found that the expression of Δ113p53 is activated in cardiomyocytes at the resection site in the zebrafish heart in a full-length p53- and ROS signalling-dependent manner. Cell lineage tracing showed that Δ113p53 -positive cardiomyocytes undergo cell proliferation and contribute to myocardial regeneration. More importantly, heart regeneration is impaired in Δ113p53 M/M mutant zebrafish. Depletion of Δ113p53 significantly decreases the proliferation frequency of cardiomyocytes but has little effect on the activation of gata4 -positive cells, their migration to the edge of the wound site, or apoptotic activity. Live imaging of intact hearts showed that induction of H 2 O 2 at the resection site is significantly higher in Δ113p53 M/M mutants than in wild-type zebrafish, which may be the result of reduced induction of antioxidant genes in Δ113p53 M/M mutants. Our findings demonstrate that induction of Δ113p53 in cardiomyocytes at the resection site functions to promote heart regeneration by increasing the expression of antioxidant genes to maintain redox homeostasis.